Wire mesh-based heat transfer enhancement in absorber tube of solar collector-An experimental study - Pooja Raval; Bharat Ramani; Nikhilkumar Jagjivanbhai Chotai; Karan Motwani (International Journal of Thermofluids)
Urbanization and technological progress have intensified the demand for energy efficiency, prompting a shift towards renewable sources like solar energy. Among solar technologies, the parabolic trough collector stands out for capturing sunlight efficiently. Various methods, including optical concentration and improved fluid heat transfer, are employed to enhance the performance. This study investigates the thermal enhancement in the absorber tube of a parabolic trough solar collector using inserts like wire mesh twisted tape and circular ring wire mesh. Thermal oil Sigma therm K is taken as a working fluid at a constant mass flow rate of 0.18 kg/s. Parameters considered include Nusselt number, friction factor, and performance evaluation criteria for assessing the performance of inserts. Absorber tube made of copper with an internal diameter of 22 mm and 1300 mm length were taken. Wire mesh twisted tape of pitch 80 mm and circular ring wire mesh of diameter 18 mm have been tested. Experiments were conducted inside the laboratory with three different configurations, i.e., plain tube, wire mesh twisted tape, and circular ring wire mesh, for a duration of 50 min. The result reveals that circular ring wire mesh exhibits the highest thermal enhancement compared to wire mesh twisted tape and plain tube. The PEC of wire mesh twisted tape is 1.17, and the PEC of circular ring wire mesh is 1.34, proving the wire mesh inserts' efficacy. These findings validate the effectiveness of augmentation techniques that can be implemented to improve the performance of the solar collector.